NEW INTERPRETATION OF THE ORIGIN OF TIGER'S-EYE - Heaney P.J.; Fisher D.M. (My University, 2003)
Tiger's-eye is an attractive and popular gemstone that is ubiquitous in stores that cater to rock and mineral collectors. For more than a century, textbooks and museum displays have identified the material as an archetype of pseudomorphism, i.e., the replacement of one mineral by another with the retention of the earlier mineral's shape. Our study has revealed that the textures responsible for the shimmer of tiger's-eye do not represent pseudomorphic substitution of quartz after preexisting crocidolite asbestos. Rather, we argue that tiger's-eye classically exemplifies synchronous mineral growth through a crack-seal vein-filling process.
Keywords: PRECIOUS STONES; MINERALS; STUDIES